Modeling multiple linear regression analysis in the formation of biogas pressure - Basirun, Basirun; Hirzi, Ristu Haiban; Muanah, Muanah (Jurnal Agrotek Ummat, 2023)
Fossil energy reserves to date are dwindling inversely proportional to the amount of consumption. So to overcome this problem, alternative energy is needed, one of which is biogas which is sourced from organic waste. The biogas production process has so far experienced many obstacles so that the formation of pressure has not been optimal. The aim of the research was to create a model to see the magnitude of the influence of humidity and temperature on the pressure of the biogas produced. The method used is multiple linear regression with the following stages, identifying variables, testing classical assumptions, model building, and model goodness. Based on the results of the analysis, the model Y ̂=17.029-0.042X_1+3.480X_2 is obtained. Simultaneous test results show that simultaneously humidity and temperature have a significant effect because the sig is 0.000<α(0.05). The results of the partial test (T-Test) of each variable also showed significant results on biogas pressure because the sig was 0.000<α(0.05). The coefficient of determination of 0.8180 means that humidity and temperature variables affect the formation of biogas pressure by 81.80% and the rest is influenced by other factors such us pH, C/NRatio, starter, and so on.